2001
DOI: 10.1002/mds.1122
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pallidal stimulation for idiopathic segmental axial dystonia advanced from meige syndrome refractory to bilateral thalamotomy

Abstract: Meige syndrome is an adult-onset dystonic movement disorder that predominantly involves facial muscles, while some patients with this syndrome develop spasmodic dysphonia and dystonia of the neck, trunk, arms, and legs. We report that all dystonic symptoms that had been refractory to both pharmacotherapy and bilateral thalamotomy were markedly alleviated by bilateral pallidal stimulation in a patient with segmental axial dystonia advanced from Meige syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 27 publications
5
61
0
3
Order By: Relevance
“…Since Vercueil and coworkers 3 first reported their results of bilateral GPi DBS in a patient with Meige syndrome, several studies have shown that segmental dystonia responds to GPi DBS. 2,3,6,9,11,13,[18][19][20][21][22][23][24][25][29][30][31] The reports on Meige syndrome and its response to DBS are primarily single cases, aside from the excellent report by Ostrem and colleagues 25 ( Table 3). The follow-up time frame has been somewhat limited in most reports, except the cases of Loher et al 21 at 7 years, Hebb et al 11 at 5 years, and Capelle and associates 6 at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Vercueil and coworkers 3 first reported their results of bilateral GPi DBS in a patient with Meige syndrome, several studies have shown that segmental dystonia responds to GPi DBS. 2,3,6,9,11,13,[18][19][20][21][22][23][24][25][29][30][31] The reports on Meige syndrome and its response to DBS are primarily single cases, aside from the excellent report by Ostrem and colleagues 25 ( Table 3). The follow-up time frame has been somewhat limited in most reports, except the cases of Loher et al 21 at 7 years, Hebb et al 11 at 5 years, and Capelle and associates 6 at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…15 Meige syndrome has become the most common eponym current used in the literature. 2,3,6,9,11,13,21,23,24,27,30 Meige syndrome is characterized by blepharospasm, cervical dystonia, and facial oromandibular dystonia. The underlying cause of Meige syndrome is unknown, but most investigators consider it a variant of idiopathic torsion dystonia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, the remaining group of patients showed good benefit from DBS and eventually no longer needed to turn on the neurostimulator. For some DBS patients with dystonia, discontinuing stimulation resulted in a clinical rebound effect with acutely severe symptoms, 109,117,118 whereas in other patients motor signs took hours, days, months, and in some cases years to return (B. Walter, personal communication). Although it is possible that stimulation could form a functional lesion in the tissue surrounding the active electrode contact or contacts, post mortem histology of DBS patients does not support this argument.…”
Section: Variability In Long-term Outcomementioning
confidence: 99%